2018
DOI: 10.1002/crat.201800069
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Electromagnetic Interference Shielding Effectiveness of CZ Grown Ge Optical Windows

Abstract: In this study, different Ge IR optical windows are produced and their electromagnetic interference (EMI) shielding performances are investigated. Three Ge single crystals with different doping concentrations are grown by the Czochralski (CZ) technique. Optical windows are obtained after the slicing, lapping, and polishing processes are examined. Formation of (111)-oriented single crystal is observed from the X-ray diffraction (XRD) pattern. In addition, IR transmission of the crystals is measured around 45% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Both Si and Ge are indirect bandgap semiconductors with bulk bandgaps of 1.11 eV and 0.66 eV at room temperature [1,2]. Si being economical and abundantly available [3] have been used in large amounts in diodes [4], semiconductor processors [4], commercial photovoltaic panels [5] while Ge has seen relatively small demands in wide range of more sophisticated and efficiency-driven application like transistors [2], satellite solar cells [6], fast switching diodes [7], infrared optics [8], electromagnetic shielding [9], thermal imaging sensors [10], and solid-state electronic devices [11,12]. This wide range of Ge based application is due to its high electrical conductivities [13] and highly tunable band gap through quantum confinement effects [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Si and Ge are indirect bandgap semiconductors with bulk bandgaps of 1.11 eV and 0.66 eV at room temperature [1,2]. Si being economical and abundantly available [3] have been used in large amounts in diodes [4], semiconductor processors [4], commercial photovoltaic panels [5] while Ge has seen relatively small demands in wide range of more sophisticated and efficiency-driven application like transistors [2], satellite solar cells [6], fast switching diodes [7], infrared optics [8], electromagnetic shielding [9], thermal imaging sensors [10], and solid-state electronic devices [11,12]. This wide range of Ge based application is due to its high electrical conductivities [13] and highly tunable band gap through quantum confinement effects [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Ge thin films have been developed using chemical vapor deposition (CVD) [9], atomic layer epitaxy [19], thermal evaporation [20], ion beam [21] and electron beam evaporation techniques [22]. Among them, S Mathur et al reported core/shell Ge wires synthesized through CVD using Ge(C 2 H 5 ) 2 [2].…”
Section: Introductionmentioning
confidence: 99%